Medical expenditures in Division I collegiate athletics: an analysis by sport and gender - Kaeding, C. C.; Borchers, J.; Oman, J.; Pedroza, A. (The Physician and Sportsmedicine, 2014)
Objective: Medical expenses for collegiate athletics include providing a training room with its supplies, equipment, personnel costs, and insurance coverage. Additional expenses beyond the training room include imaging, diagnostic testing, specialty consultations, and surgeries. We hypothesized that there would be no difference in average expenses or number of claims between male and female athletes over a 5-year period. Design: Prospective patient cohort. Setting: A sports medicine center serving athletes in Big 10 Conference intercollegiate sports. Assessment of Risk Factors: All medical claims and charges for 36 varsity teams were analyzed from 2005 to 2010. The teams were categorized into 3 groups: female-only teams, male-only teams, and coed teams. Analysis of sports with corresponding male and female teams was also performed. Main Outcome Measurements: Claims and charges for medical care for 36 intercollegiate athletic teams over 5 years. Results: Individual team claims and charges were stable over the study period. In 11 of the 14 sex-matched sports, the female teams had higher average annual charges. After normalizing for roster size in the sex-matched sports, females had 0.97 more average annual claims (P < 0.01) and $1459 higher annual charges (P = 0.001) than their male counterparts. The charges per claim were similar between the sexes. The 5 teams with the highest average annual charges were football, wrestling, softball, women's crew, and men's lacrosse. When normalized for roster size, the 5 sports with the highest average annual charges per athlete were softball, women's diving, men's basketball, wrestling, and men's gymnastics. Conclusion: Charges per claim were similar between the sex-matched sports, but the female sports had a higher number of annual claims per athlete and thus higher total charges per athlete/year. Football had the highest average annual total charges as a team, but when normalized for roster size football charges per athlete/year were similar to those of other sports.